Penyelenggaraan Pendidikan Karakter di Raudatul Athfal (RA) Darussalam Kota Bogor - Umul Hidayati (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2016)
This research is aimed at acknowledging the success level of implementation of Character Education program in Raudhatul Athfal (RA) Darussalam Institution, Bogor Barat District, Bogor City, West Java Province. This research uses qualitative method with phenomenological and socio-historical approaches. This research results in finding that the character education in RA Darussalam can be implemented properly and has reached its maximum output. The indicator of this success is the students’ capability to absorb and implement the Islam Religion Education materials, which include faith, morals, observance, al-Qur’an and hadiths, as well as good characters. Whereas the supporting factors are, among others, the use of appropriate learning approach and method, the occurrence of learning method diversification, the development of curriculum combining national curriculum, RA-specific curriculum that is full of Islamic teaching values, and characterbased curriculum, the presence of competent and qualified educators graduated from Bachelor Degree (S1) program majoring in Early Aged Children Education, and the provision of complete learning facilities. The impact of this character education implementation success can be felt in the sociological, psychological and political aspects, both for the RA management and parents of students as can be seen from the emerging feeling of content and satisfied for the achieved education output, the increasing public interest in RA, the increasing self-confidence and spirit of the educators in performing their teaching duties, the emerging attention of the government (Ministry of Religious Affairs in the Bogor City) towards this institution.